2013
DOI: 10.2320/matertrans.h-m2012832
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior and Texture Formation in AZ80 Magnesium Alloy during Uniaxial Compression Deformation at High Temperatures

Abstract: High temperature uniaxial compression deformation is conducted on AZ80 magnesium alloy at 673 and 723 K by varying the strain rates ranging from 1.0 © 10 ¹4 to 5.0 © 10 ¹2 s ¹1 in order to investigate the behaviors of deformation and texture formation. Particular attention is paid to the development of basal texture. Under the deformation conditions of this study, work softening is observed in all the stressstrain curves without exception. The results of the microstructure observation reveal occurrence of dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This means that strain rate can affect the mechanism of dislocation movement. It has been reported and discussed that the creep mechanism has high relationship with this phenomenon in AZ80 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that strain rate can affect the mechanism of dislocation movement. It has been reported and discussed that the creep mechanism has high relationship with this phenomenon in AZ80 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, even if the number of activated slip systems satisfies the von Mises criteria and can accommodate the deformation, if one of the slip systems is receiving higher stress than that of its family system, the crystal rotation would shift toward its direction [ 21 ]. Results of AZ31 plane strain compression have shown that when their activated slip systems set as the prismatic <a>, but each slip system is in a non-equilibrium state, their texture component rotates during the strain is becoming increased [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Moreover, Fukutomi et al conducted researches using magnesium alloys with different contents in alloy, such as AZ series magnesium alloys. [13][14][15] Through these results, the formation of textures can be controlled by the variation of deformation factors such as solute atoms, deformation rate, and temperature. Considering that these factors are influenced by the activity of dislocations, they can also affect the control of damping performance.…”
Section: Of 11mentioning
confidence: 97%
“…In addition, the development of texture orientation in magnesium alloy is known as a factor that has a great influence on plasticity anisotropy or workability compared to other alloys [ 12 , 13 ]. One of authors conducted research using magnesium alloys with different Al contents in alloy, such as AZ series magnesium alloys [ 14 , 15 ]. Through these results, the formation of textures can be controlled by the variation in deformation factors such as solute atoms, deformation rate, and temperature.…”
Section: Introductionmentioning
confidence: 99%